Post-mortem analysis of prescription opioids—A follow-up examination by LC–MS/MS with focus on fentanyl. (December 2019) - Schönfeld, T.; Heinemann, A.; Schulz, M.; Gradl, G.; Andresen-Streichert, H.; Müller, A.; Iwersen-Bergmann, S.
Highlights: Changes in the analytical strategy resulted in considerable changes of detection rates of prescription opioids. Detection of prescription opioids in drug-related deaths cases is mostly concomitant to methadone. Medico-legal autopsy seems to be a sensitive indicator for opioid intoxications. Fentanyl was consumed orally, by smoking and intravenous. Detection of fentanyl is rare in Hamburg in drug-related deaths cases. Abstract: Our aim was to investigate the reason for relatively low detection rates for opioids and fentanyl in particular in post-mortem cases in the State of Hamburg. We re-analysed 822 blood samples from two different time periods, 2011/12 and 2016. These samples had been previously analysed in accordance with post-mortem routine by a case selected strategy. All samples were re-analysed with an LC–MS/MS method specific for prescription opioids. The main point in the evaluation was to determine whether the previous analysis strategy had led to underreporting of drug-related deaths (DRD), especially with regard to fentanyl. Another aim was to evaluate changes in prescribing prevalence of opiates and opioids. We compared pharmacy claims data in Hamburg with Germany. The analyses showed that the number of DRD remained unaffected by the new analytical strategy. Detection rates in DRD, however, increased for fentanyl 3.4-fold from 1.2% to 4.1%, buprenorphine from 5.9% to 7.6%, oxycodone from 0% to 1.8%, tilidine from 1.8% to 2.4%. The most frequently detected opioids in DRD cases were methadone (39.4%) and heroin (20%). Prescription rates between 2011–2017 decreased in Hamburg for nearly all opioids, morphine by - 43.5%, buprenorphine - 43%, codeine - 57%, fentanyl - 25%, tilidine -17%, tramadol - 31%, and hydromorphone -6%. Oxycodone, tapentadol, and piritramide prescription rates increased. For Germany, a decrease in the prescription rates for fentanyl was also found during this period (-12.9 %), although not as pronounced as in Hamburg. Prescription rates for methadone were three to greater than five times higher in Hamburg as compared to the German average due to the higher number of substituted persons per inhabitant. Conclusion: Despite the global problem of opioid abuse, there are significant regional differences in the nature and extent of opioid abuse. It is necessary to collect data at the national level to develop appropriate prevention strategies.